A Guide to Citrus Mite Identification - Stephen H. Futch; C.C. Childers; C.W. McCoy (EDIS)
This document provides insights into the Citrus Rust Mite (CRM), detailing its morphology, behavior, and impact on citrus crops. CRM, characterized by its piercing-sucking mouthparts, targets epidermal cells of citrus leaves, fruit, and twigs, causing surface blemishes and potential reductions in fruit size and quality. The text also discusses other mites affecting citrus, such as the Pink Citrus Rust Mite (PCRM), Citrus Red Mite (RM), Texas Citrus Mite (TCM), and Six-Spotted Mite (SSM), outlining their distinctive features and damage patterns. Understanding these mites and their effects is crucial for effective pest management in citrus cultivation.